Process Parameters Optimization in Gas Blow Forming of Pin-type Metal Bipolar Plates using Taguchi and Finite Element Methods - M. Moradian; A. Doniavi; V. Modanloo; V. Alimirzaloo (International Journal of Advanced Design and Manufacturing Technology, 2017)
Metal bipolar plates are the most important parts of the fuel cells and recently these plates are used instead of graphite ones.In the present study, gas blow forming of a pin-type aluminum 5083 bipolar plate has been studied. After the simulation of the process, the FE model has been validated using experimental results. Then, the effects of parameters including maximum pressure of the gas, pressurization profile and corner radius of the pin on thinning ratio and forming depth of final part have been investigated. Nine experiments were designed using the Taguchi L9 orthogonal array and the experiments were performed using the FE model. The signal to noise (S/N) ratio and the analysis of variance (ANOVA) techniques were carried out to determine the effective parameters and the contribution of each parameter. The maximum pressure of 1.2 MPa, SP2 pressurization profile and corner radius of 0.2 mm lead to the minimum thinning ratio. Also, it was found that to maximize the forming depth, the maximum pressure of 2 MPa, SP1 pressurization profile and corner radius of 0.3 mm should be selected. Also, ANOVA analysis showed that the most significant parameters on thinning ratio and forming depth are corner radius and maximum pressure, respectively.